Diagnostic and Identifical study of Turkey (Meleagris gallopavo) Parasites in AL-Diwaniyah province - MadloolAlmayali, Hadi; Abdulzahra Al shabani, Hind (Al-Qadisiyah Journal of Pure Science, 2018)
The current study during the period between thefirst of the September 2014 carrid out end of May 2015 50. birds of domestic turkey Meleagrisgallopavowas collested from different areas of Al- Diwaniya city markets , to isolating and identification the external and internal parasites parasitized on these birds as well as study the incidence of parasites and intensity and the most important pathological changes and histological changes resulting from external intestinal infections sex species of external parasiteswas isolated included four species of biting lice Gonoiocotesgallina , Goniodesgigas , Menacanthusstraminus and Oxylipeurus sp. Theinfection rateand severityof 10%, 6,81,4%, 4,72,2,%, 54.2%, 0.09, respectively, and Two species ofTicksareArguspersicusandHaemophysalissp Nymph.and the severity ofinfectionwas 2%, 0.36; 2%, 0.24: respectively. The resultsshowedthat the tripleinfection ofliceare the mostcommon,( 63.63%.) Theinternal parasites9species ofintestinalparasiticwormsin the digestive systemincludedtwo species ofProtozoa Eimeriasp. andHistomonasmeleagridisTheinfection rate and severitywas14%, 4.200.2%, 0.14, respectively, and 4species oftapeworms Cesticillusrailletina,Tetragonarailletina , Choanoyania infundibulum and HymenolepisspThe severity ofinjurywas2%, 100.2% 53.284, 4,00,2% 2%, 0.42; Respectively, three species ofnematodesAscardiagallinarum , Capillaria sp. and gallinarumheterakis and severity ofinjuryandamounted to21.73%, 1.2; 2%0.100; 17.79%, 1.25; . The study showed the presence of internal parasites ofwormssitesin the gastrointestinal tractit was observed thatmost oftapewormsparasitizein the small intestineat rateshigher thanwhatis found inother parts ofthe gastrointestinal tract, and the Alaptdaiaatare foundin the liverand small intestine. Thenematodesare also foundin variousparts of thegastrointestinal tract, including bothof the small intestineand thelarge intestineandesophagus. thespecies Haemophysalis sp. and Oxylipeurus sp. and helminthsRaillietinacesticillus ,Raillietinatetragona ,Choanotaniainfundibulum,Hymenolepissp.Ascardiagallinarum ,Capillariasp.Heterakisgallinarum .Eimeriasp first recording in turkeys in Iraq.Also the current study showed a many of gross and microspcopic pathological changes caused by lice in infected birds, such as lethargy, laziness and sagging wings and nervous tension and break the feathers and hair loss, as well as change the color of the skin.also appeared many of the macroscopic and microscopic changes in the gastrointestinal tract as a result of, intestinal worm included changes macroscopic obstruction and hemorrhagic bruises and blood infiltration The microscopic changes have included the infiltration of inflammatory cells Nicrosis and abstraction of cells lining the of these channels and the proliferation of Kubffer cells and expansion in sinosoids and atrophy of the villi tissue.